The Effect of Psychological and Non-Psychological Support on Relationship Satisfaction In Close Friendship - Siti Nur Fatihah; Cosmas , Getrude (Jurnal Psikologi dan Kesihatan Sosial, 2025)
Friendships play a crucial role in university students’ well-being, particularly in their relationship satisfaction. This is more prominent when physical distance from family limits access to emotional and practical supports. To explore this phenomenon, a study was conducted to examine the effects of both types of support on relationship satisfaction among close friends in a university setting. A total of 203 undergraduate students took part in this study. Most participants were female (n=138, 68%), while the remaining are male (n=65, 32%). The study found that both psychological and non-psychological support contributed significantly and positively to relationship satisfaction. The more students received both supports, the more satisfied they were with their satisfaction in friendships. This study showed a combination of empathy, encouragement, and helpful actions contributes to stronger and more fulfilling friendships. The results can help guide peer support initiatives and encourage students to offer and seek various types of support to maintain healthy and satisfying friendships.